2011
DOI: 10.1002/ange.201103717
|View full text |Cite
|
Sign up to set email alerts
|

Sr3[Co(CN)3] and Ba3[Co(CN)3]: Crystal Structure, Chemical Bonding, and Conceptional Considerations of Highly Reduced Metalates

Abstract: Überraschende Eigenschaften hält der trigonal‐planare Komplex [Co(CN)3]6− bereit (siehe Strukturbild; Co rot, C grau, N grün, Erdalkalimetall‐Gegenionen gelb). Bindungslängen und Ladungen der CN‐Liganden variieren, und das Co‐Zentrum verfügt über eine geschlossenschalige (d10‐)Konfiguration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 17 publications
(5 reference statements)
0
15
0
Order By: Relevance
“…However, the CÀN distances and n CN values of the known cyanometalates have proven remarkably invariant. [5,7] Hçhn et al have now reported [8] a completely documented case of reduced cyanide, that is, three CN 1.67À ions stabilized by cobalt(ÀI) in M 3 [Co(CN) 3 ] (M= Sr, Ba). Remarkably, the material was obtained by a high-temperature ( % 1200 K) "solid-state" route and not by a less harsh coordination chemistry procedure.…”
Section: Reduction Of Cnmentioning
confidence: 97%
See 4 more Smart Citations
“…However, the CÀN distances and n CN values of the known cyanometalates have proven remarkably invariant. [5,7] Hçhn et al have now reported [8] a completely documented case of reduced cyanide, that is, three CN 1.67À ions stabilized by cobalt(ÀI) in M 3 [Co(CN) 3 ] (M= Sr, Ba). Remarkably, the material was obtained by a high-temperature ( % 1200 K) "solid-state" route and not by a less harsh coordination chemistry procedure.…”
Section: Reduction Of Cnmentioning
confidence: 97%
“…The absence of ligand-field effects in a d , the high negative charge of which is offset by three dipositive cations. A low, but not excessively negative oxidation state for cobalt was also suggested by density of states (DOS) calculations and the quantum theory of atoms in molecules (QTAIM) approach, [8] which yielded approximate charges of + 1.4 (Ba), 0.0 (Co), and À1.4 (CN). [8] Figure 1).…”
Section: Reduction Of Cnmentioning
confidence: 98%
See 3 more Smart Citations